2022
DOI: 10.1002/smsc.202100124
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin Inhibits SARS‐CoV‐2 by Targeting Its 3C‐Like Protease

Abstract: The current COVID‐19 pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), is an enormous threat to public health. The SARS‐CoV‐2 3C‐like protease (3CLpro), which is critical for viral replication and transcription, has been recognized as an ideal drug target. Herein, it is identified that three herbal compounds, Salvianolic acid A (SAA), (–)‐Epigallocatechin gallate (EGCG), and Oridonin, directly inhibit the activity of SARS‐CoV‐2 3CLpro. Further, blocking SARS‐CoV‐2 infectivity by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Here, we screened a compound with significant inhibitory activity against EV71 3C pro based on a library of traditional Chinese medicine monomer compounds, SA. And, SA with its structural analogue (−)-Epigallocatechin gallate (EGCG) was reported to have significant inhibitory effect on SARS-CoV-2 Frontiers in Pharmacology frontiersin.org 3C pro (Supplementary Figure S4) (Zhong et al, 2022). Also, the predicted targets of SA using SwissTargetPrediction showed that the protease was the predominant target of SA action (Supplementary Figure S5), and these results further support the molecular mechanism of SA as a viral protease inhibitor.…”
Section: Discussionmentioning
confidence: 57%
“…Here, we screened a compound with significant inhibitory activity against EV71 3C pro based on a library of traditional Chinese medicine monomer compounds, SA. And, SA with its structural analogue (−)-Epigallocatechin gallate (EGCG) was reported to have significant inhibitory effect on SARS-CoV-2 Frontiers in Pharmacology frontiersin.org 3C pro (Supplementary Figure S4) (Zhong et al, 2022). Also, the predicted targets of SA using SwissTargetPrediction showed that the protease was the predominant target of SA action (Supplementary Figure S5), and these results further support the molecular mechanism of SA as a viral protease inhibitor.…”
Section: Discussionmentioning
confidence: 57%
“…409 Paclitaxel also increases the alveolar capillary membrane permeability, resulting in several adverse effects, including pulmonary diffusion dysfunction, which raises concerns for COVID-19 treatment. 410 Other diterpenoids, including triptolide, 411 oridonin, 412 , 413 and carnosic acid, 414 , 415 were also identified to have anti-SARS-CoV-2 activities by computational methods.…”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 99%
“…These compounds possess catechol or Michael receptors that have the ability to covalently bind to the cysteine residues in SARS-CoV-2 M pro . 15,16,23,24 In this work, a practical strategy for rapidly discovering irreversible inhibitors of SARS-CoV-2 M pro from complex components (such as herbal extracts or compound prescriptions) was demonstrated. Our approach integrates target-based high-throughput screening and mass spectrometry (MS)-based approaches, enabling efficient screening of the herbal medicines with potent time-dependent inhibition on SARS-CoV-2 M pro and to rapidly identify the covalent M pro inhibitors from crude herbal extract (Figure 1).…”
Section: Several Virus-based and Host-based Targets Have Been Validatedmentioning
confidence: 99%